Hypnosis in Islamic Perspective (An Analysis of Bin Baz's Fatwa) - Adnan Yusufi (Ijtimā`iyya: Journal of Muslim Society Research, 2017)
In the last decade, a hypnosis approach for various purposes in the life of society is already commonly used. There are some people who use it in the scope of the families such as hypnobirthing, hypnoparenting, etc, and the other one uses it in the field of education such as hypnolearning, hypnoteaching, etc. However, when reviewing the fatwa of Bin Baz, one of the great Islamic Scholars from saudi Arabia there is a prohibition on the use of hypnosis. The main aim of this study is to analyze the contents of Bin Baz’s fatwa relation to the practice of hypnosis in the field of education. The research method that the author use is the study of literature with an analytical approach of documents that is descriptive qualitative. Data is collected through observation and documentation, then analysis for the content. While the thinking framework, which is used, are deductive, inductive, and comparative methods. The main conclusion from the results of this study that the Bin Baz’s fatwa about hypnosis is weak or less because it has fewer arguments can be accounted for. There are a few things that have ambiguous meanings; especially the word hypnosis itself is being converted into "magnetic sleep." Through a study based on the latest science, expected quality of human resources especially in the field of education may continue to increase, as well as should be able to answer the problems of society.